Ecojogo: produção de jogo didático e análise de sua contribuição para a aprendizagem em educação ambiental - Silva, Rafael Bezerra e (2015)
The didactic games such as laboratory practices, outdoor class, movies and videos are different methodological possibilities which can be used for address the contents biology (BRASIL, 2006). For Campos et al. (2002), the didactic games deserve much more space in the practice of teach, because they are an important alternative to get and retain the knowledge through a clime of joy and pleasure. Nowadays, the main claim of the Secondary School has been the preparation of students for ENEM, which is the main way to enter in the university in Brazil. In the last three editions of the ENEM, about 40% of the Biology’s questions were related to ecology and environmental education. According to Auad (2005), the environmental education is an urgent social problem. Because of the relevance of this issue presented, this study had as a general objective to create a didactic game and analyze its contribution as a tool for learning environmental education. For the achievement of this research, an outdoor study was made with approach in quality, quantity and applied nature, as well was developed a didactic game board with questions and answers about environmental educational named Ecojogo. The game was prepared and used in three lessons by students from a 3rd grade state public Secondary School in the town Crateús-CE. The data collection was carried out by watching partakers and the application of questionnaires. During the usage of the Ecojogo in the classroom, it was noticed that the use of the game created a pleasant teaching and learning environment, because of the interaction between players and the funny process of the game. From the analysis of the questions applied, was verified that the student’s knowledge increased in an average of 34% after using the game. Related to the evaluation of Ecojogo in didactic games held in Scientific event, everyone answered that they would use the game in the teaching of environmental education classes, because it is attractive relevant topics. According to those people who were interviewed, the Ecojogo helps to understand, stimulates thinking and provides a significant capacity, because it approaches the contents in context with problem situations. Although recognizing the importance of contextualization for understand the contents and preparation for ENEM, some peoples who was interviewed, reported that this feature slows the departure dynamic, because of the size of the questions. Based on the survey’s results, it was concluded that the Ecojogo is an efficient methodological strategy for learning environmental education, and that teachers should invest in development and usage of didactic materials for teaching Biology. Besides of developing and using didactic materials, it is also necessary spread and share products and materials produced in successful experience, in order to this knowledge be released and, thus, improved.